Produksi Biodisel dari Minyak Jelantah Menggunakan Katalis Asam padat (Nafion/SiO2) - Mahreni Mahreni (Eksergi, 2010)
Production of biodisel from waste cooking oil (WCO) was performed using a double catalyst Nafion/SiO2 as esterification catalyst and NaOH is used as transesterification catalyst . Study was conducted through three stages:as well as  synthesis of Nafion/SiO2 solid acid catalyst, the synthesis of biodisel using a single catalyst (NaOH) and the synthesis of biodisel using a catalyst (Nafion/SiO2 and NaOH). Solid acid catalyst is made of Nafion 5 wt.% solution and the (Tetra Ethoxy Ortho silicate, TEOS) using solution phase sol-gel method to produce Nafion/SiO2. Furthermore Nafion/SiO2 was applied as esterification catalyst. Esterification reaction conditions at temperatures of 75oC and fixed reaction time of 45 minutes. The reaction is run at three-neck flask equipped with a stirrer, thermometer and cooling water. Products are separated and the upper layer is used as a reactant of transesterification reaction using NaOH catalyst and results biodisel (FAME). Result analysis of physical properties, ie viscosity, density and flash point FAME meets the standard requirements of biodisel. Chemical characterization in the FAME show there are more than six kinds of methyl esters indicate that FAME was formed. The percentage of biodisel that is produced by using dual catalyst is higher compared to using a single catalyst proved that the solid acid catalyst plays an important role in converting the free fatty acid in to ester in the WCO.